The Oxford handbook of police and policing - Reisig, Michael Dean, 1968-; Kane, Robert J. (Oxford handbooks in criminology and criminal justice., 2014)
The police are perhaps the most visible representation of government. They are charged with what has been characterized as an ""impossible"" mandate -- control and prevent crime, keep the peace, provide public services -- and do so within the constraints of democratic principles. The police are trusted to use deadly force when it is called for and are allowed access to our homes in cases of emergency. In fact, police departments are one of the few government agencies that can be mobilized by a simple phone call, 24 hours a day, 7 days a week